Antidiabetic potential of andaliman: Histopathological and glycemic improvements in diabetic rats - Simbolon, Boyke Marthin; Lina, Juliana; Saragih, Ayu Theresia; Bangun, Chrismas Gideon; Nasution, Muhammad Fauzi; Rosari, Anita; Dewani, Yunita; Syahputra, Imam; Silalahi, Todung Donald Aposan (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia and pancreatic dysfunction, particularly involving the Islets of Langerhans. Andaliman (Zanthoxylum acanthopodium) is a plant rich in flavonoids and antioxidants, which are believed to have antidiabetic effects. This study aimed to evaluate the effectiveness of the ethanol extract of Andaliman fruit on pancreatic histopathology in alloxan-induced diabetic rats. Methods: This study employed a true experimental design with a pre-test and post-test control group structure. Twenty-four male Wistar rats were randomly assigned to six groups: a normal control, a positive control (metformin 9 mg/kg), a diabetic control (alloxan 90 mg/kg), and three treatment groups induced with alloxan followed by administration of Andaliman extract at doses of 150, 250, and 350 mg/kg body weight, respectively. Treatments were administered for 14 days, after which blood glucose analysis (pre- and post-treatment) and pancreatic histopathological assessments were performed. Results: Statistical analysis revealed a significant reduction in blood glucose levels following treatment (p = 0.001). Histopathological examination showed that Andaliman extract ameliorated alloxan-induced damage to the Islets of Langerhans. The 350 mg/kg body weight dose resulted in the most pronounced tissue regeneration compared to the other treatment groups. Conclusion: The ethanol extract of Andaliman fruit effectively improves pancreatic histopathology and lowers blood glucose levels in diabetic rats.